PENINGKATAN HASIL BELAJAR IPS SISWA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE (TPS) DI KELAS V - Yeni, Zaria Fitri; Nasrul, Nasrul; Dalais, Mursal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The aim of the research is to describe the improvement of students learning outcomes in learning Social Science Subjects by using the Think Pair Share model at  grade of Elementary School. The classroom action research was conducted in the research by using both qualitative and quantitative approach. The subject of the research were 24 students of the school (11 male students and 13 female students). This research was conducted in two cycles consisted of planning, acting, observing, and reflecting. The result of the research shows that there are some improvement: a) The lesson plan increased from 75% in cycle I to 92,86% in cycle II, b) the teacher teaching aspect increased from 77,08% in cycle I to 91,67% in cycle II, the students learning aspect also increased from 70,84% in cycle I to 87,50% in cycle II, c) the students learning outcomes increased from 74,97 in cycle I to 86,73 in cycle II. Thus, the use of Think Pair Share Model has improved the students learning outcomes in learning Social Science at  grade of SDN 51 Bungo Pasang, Padang.  Keywords : Learning outcomes, Learning Social science, Think Pair Share